Criminal Offense or Civil Law Dispute: to the Issue of Assessing Unfair Information Business under the Criminal Legislation of Ukraine - Yevtieieva, Daryna (Teisė, 2022)
The article provides a criminal assessment of unfair information business (“information fraud”). Based on the analysis of the Supreme Court’s positions and through the prism of such manifestations as nonfulfillment of obligations and improper fulfillment of obligations (untimely, incomplete and poor-quality fulfillment of obligations in the form of service), it is determined whether this phenomenon falls under criminal fraud within the legislation of Ukraine.
Keywords: information fraud; information product; criminal offense; fraud; deception; breach of trust